2018
DOI: 10.1159/000486173
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Adipose Tissue and Muscle Mass Based on Computed Tomography Scans: Comparison of Eight Planimetric and Diametric Techniques Including a Step-By-Step Guide

Abstract: Background: Recent scientific work proved that knowledge about body composition beyond the body mass index is essential. Both adipose tissue and muscular status are determining risk factors of morbidity and mortality. Analysis of single cross-sectional computed tomography (CT) images, acquired during routine care only to prevent additional radiation exposure, provide a detailed insight into the body composition of chronically and critically ill patients. Methods: This retrospective study included 490 trauma pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…However, BMI has been criticized as an unreliable estimation of fat content in the body. Thus, in addition to BMI, we also looked at both subcutaneous and visceral fat thicknesses on CT scans in our study, and this has been shown to be a more accurate approximation of total fat content [13][14][15][16]. This is the first study to utilize these tools to determine if obesity is a factor in NSTI clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, BMI has been criticized as an unreliable estimation of fat content in the body. Thus, in addition to BMI, we also looked at both subcutaneous and visceral fat thicknesses on CT scans in our study, and this has been shown to be a more accurate approximation of total fat content [13][14][15][16]. This is the first study to utilize these tools to determine if obesity is a factor in NSTI clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Two components of abdominal fat were measured, subcutaneous and visceral fat. The subcutaneous fat thickness of the abdominal wall was measured on CT at the L4/L5 lumbar vertebra as identified by the most superior aspect of iliac crest, as described previously [13,14]. Two measurements were made using the electronic medical record's measurement tool on the abdominal pannus, on either side of the vertebra.…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, anthropometric proxies can be obtained simply and a growing evidence of their diagnostic performance encouraged clinicians to use them to avoid exposing their patients to CT hazards. 4 Analyses to verify the performance of each anthropometric index as a CVD risks screening tool in adults showed that waist-to-height ratio (WHtR) is consistently better than waist circumference (WC) or body mass index (BMI). In 2008, a metaanalysis including 88,000 participants from different populations supported the evidence that WHtR is a promising tool in discriminating CVD risks related to central obesity.…”
mentioning
confidence: 99%
“…Sarcopenic obesity was defined as patients who fulfilled the skeletal muscle index (SMI) threshold for SARC as well as a BMI >25 kg/m 2 , the accepted definition of obesity in Asian cohorts . Visceral adipose tissue measurements were not used to define obesity because a standard has yet to be validated . Furthermore, using readily available BMI measurements may offer better clinical translatability.…”
Section: Methodsmentioning
confidence: 99%